Implemntasi Rencana Kerja Pemerintah Desa Dalam Pembangunan Di Desa Bonerte Kecamatan Pasimarannu Kabupaten Kepulauan Selayar - Ratu, Andi; Ansyari, Muh Isa; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine how successful the implementation of the village government work plan in development in Bonerate Village. This study used qualitative research. Data collection techniques used observation, interviews and documentation. Data analysis used the theory of Jan Marse, which consisted of four things that influenced policy implementation, namely information, policy content, community support, and potential sharing. The result of this research showed that the implementation of the village government work plan in the development of Bonerate Village had not been optimally realized, because there was lack of public understanding of information about village work plans, there were other influencing factors such as the content of policies that were not right on target, lack of community participation or community support in development. Inadequate Village and Village Potential. Keywords: Implementation of Village RKP Policy, Development